If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 79 = 5y + -7 Reorder the terms: 79 = -7 + 5y Solving 79 = -7 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 79 + -5y = -7 + 5y + -5y Combine like terms: 5y + -5y = 0 79 + -5y = -7 + 0 79 + -5y = -7 Add '-79' to each side of the equation. 79 + -79 + -5y = -7 + -79 Combine like terms: 79 + -79 = 0 0 + -5y = -7 + -79 -5y = -7 + -79 Combine like terms: -7 + -79 = -86 -5y = -86 Divide each side by '-5'. y = 17.2 Simplifying y = 17.2
| 5(x-2)-3x-1=391 | | (5x)+3=-2 | | 17=3v | | 5(3x-2)-4x=12 | | 5(x-9)=2(x-4) | | 20x+17=337 | | u+2=3 | | 3(x-2)=4(y+3) | | g-27=-19 | | 6(x+2)-4=5x+8 | | (7x^3)(3x+5)=0 | | 3x-7x=20x-3 | | 4x-28=x-2 | | 64=-10v+4 | | 4x-x+7x=9 | | 7x-8=5x+2x+10 | | 1.1x-0.4x-225000=0 | | 2x-3-9=-x | | 2-7y+5=4y+15-7y | | 5x+4(x-6)=12 | | 5(x-4)+2x=7x-1 | | 15-(x+6)=3x-7 | | 3+4x=5x-6 | | 4v+40=8(v+7) | | 3x-8x+6=7x-1 | | 10+10=(208)+10 | | 2n+6=-10 | | 3.25-y=-0.75 | | Z=4+7i | | 4x+(x-3)6=92 | | 3.25-y=0.75 | | F(x)=-x^2+3x-2 |